Sosialisasi Pemanfaatan Limbah Sambah Organik Dapur Menjadi Eco-Enzyme - Bagas Mustakim; Adhiputro Pangarso Wicaksono (Muria Jurnal Layanan Masyarakat, 2022)
Eco-enzyme is a versatile liquid produced from fermenting kitchen waste for 3 months with brown sugar or molasses or molasses liquid with organic kitchen waste such as fruit and vegetable peels using a 1:3:10 composition. The purposes of this outreach activity are to reduce the organic waste produced by the kitchen, which becomes pollution in the Dukuh Lawang RT 01 environment and to help the community to process organic waste or kitchen waste in Dukuh Lawang RT 01 easily. The benefits of eco-enzyme liquid are for cleaning floors, for disinfectants and plant fertilizers.